PERANCANGAN SISTEM INFORMASI ADMINISTRASI PADA YAYASAN DRS. H. SYEIKH ASRUL BAKAR CABANG KOTA JAMBI BERBASIS WEBSITE - Ahmad Louis (JURNAL AKADEMIKA)
Technology plays an important role in improving the quality of an institution. Users not only as an automation process to access information, but also creates the speed, accuracy and completeness of a system that is integrated, so that the process is going to be an efficient organization, the structure and flexible. Developments in information technology today not only used for large-scale instsani agencies, but can be used by various circles of society to support a business, organization, or business manag ement. One current example is the development of information in an organization